OCEANARIUM DESIGN WITH A CONTEMPORARY ARCHITECTURAL APPROACH IN MANADO - Freike E. Kawatu; Raffaella Sumenge; Moh. F. Suharto (Indonesian Society of Applied Science, 2023)
Oceanarium is a place for recreational and educational tourist spot, the oceanarium itself provide a place for accommodate various types of marine life, like fish to coral reefs. Manado as one of the marine tourism areas does not yet have a marine tourism instituation that is able to present recreational and educational tourism in the same place, the people of Manado themselves are not very familiar with underwater biodiversity so it needs to be introduced further so that people can be more concerned about protecting marine life, caring for and preserving the potential of this marine tourism. The design of the oceanarium with a contemporary architectural approach can make it easier for the public to reach and recognize various kinds of marine life in Manado through the oceanarium building, a contemporary architectural approach in accordance with the needs of people who like the latest recreational and educational places. The contemporary architectural approach itself is a design approach that responds to the needs of the community while developing at that time, a contemporary architectural approach that adapts to the existence of development in the city of Manado will facilitate public acceptance of new buildings. The existence of an oceanarium with an architectural approach in Manado is expected to be able to fulfill the community's needs for educational recreational buildings in order to foster a sense of care for preserving marine tourism in Manado